PROXIMATE COMPOSITION AND CARCASS QUALITY OF SMOKED AND FRESH GREY MULLET (LIZA FALCIPINNIS) COLLECTED FROM LAGOS LAGOON - Esan, Oluwayomi; Abdullahi, M. M. (FUDMA JOURNAL OF SCIENCES, 2022)
The purpose of this research was to determine the quality of smoked grey Mullet (Liza falcipinnis). The fish were divided into two portions; one portion was processed using NIOMR smoking kiln. All of smoked mullet samples were subjected to chemical analysis. The proximate composition shows that moisture content in smoked sample was very low (5.43%) while it was high (72.89 %,) in fresh sample. There was no significant difference in both smoked and fresh sample values obtained for crude protein (25.7% and 22.2%) respectively, while lipid, ash and carbohydrate values obtained shows significant difference (p>0.05). Also, there were no significant difference in the moisture and lipid values obtained for smoked tissue, whole fish, and carcass of mullet, but there were significant differences in the values obtained for crude protein, ash and carbohydrate respectively